2023
DOI: 10.1007/s11540-022-09602-8
|View full text |Cite
|
Sign up to set email alerts
|

How Kenyan Potato Farmers Evaluate the Seed: Implications for the Promotion of Certified Seed Potato

Abstract: Improving the quality of seed potatoes that smallholder farmers plant continues to represent one of the most important challenges of the potato sector in most developing countries to counter the long-lasting poor yields. This study aimed to better understand the way farmers choose seed potato by exploring the attributes they look for and the benefits they expect from them. We used means-end chains analysis in combination with Kelly’s repertory grid as an elicitation technique and disaggregated data for male an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…This has raised the pertinent question of what must be done to guarantee the availabil-ity, access and utilization of affordable quality seeds by farmers in Nigeria (Oyekale, 2014). Atieno et al (2022) reported that farmers relate 'good' seed varieties to seeds that sprout very well or of a popular variety, certified and without damage.…”
Section: Seed Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…This has raised the pertinent question of what must be done to guarantee the availabil-ity, access and utilization of affordable quality seeds by farmers in Nigeria (Oyekale, 2014). Atieno et al (2022) reported that farmers relate 'good' seed varieties to seeds that sprout very well or of a popular variety, certified and without damage.…”
Section: Seed Qualitymentioning
confidence: 99%
“…Otieno et al (2016) consented that among the preference criteria for farmers' seeds are the texture of planting material, good taste, marketability, adaptability to climate change, nature of planting material and nutritional benefits. According to Atieno et al (2022), the most preferred qualities in seed are those qualities that will increase yield and invariably lead to more farm income which will enable the farmers to attain their desired improvement in standard of living. Izuogu et al (2023), Akanbi et al (2022) and Kalsa (2019) identified some of the preference criteria for certified seeds among farmers in Nigeria to include early maturing, high yield, better cooking quality, tolerant to submergence, resistance to diseases and drought.…”
Section: Seed Preferencementioning
confidence: 99%
“…The suboptimal use of quality inputs is the result of costly farm inputs for potato production (Kaguongo et al., 2014). The cost of certified seed potatoes is among the biggest financial outlays for Kenyan smallholder farmers (Atieno et al., 2023). Using certified seed potatoes is one way of improving productivity; however, such seeds are not easily accessible to farmers and, if available, are expensive for smallholder farmers (Kwambai et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors limit the production and productivity of potato in Kenya, including limited access to quality seed of adapted and acceptable varieties (Gildemacher et al 2011;Muthoni 2014;Atieno et al 2023;Kwambai et al 2023). The Kenyan government increased the attention to potato, resulting in public-private-partnerships with European seed companies working individually or with their Kenyan counterparts in introducing high seed quality of new varieties.…”
Section: Introductionmentioning
confidence: 99%